Mitigating the biodiversity footprint of energy crops – A case study on arthropod diversity. (June 2019) - Chmelíková, Lucie; Wolfrum, Sebastian
Abstract: Rising demand for renewable resources has increased silage maize ( Zea mays L.) production characterized by intensive soil management, high fertilizer and pesticide inputs as well as simplified crop rotations. Advantages of renewable biomass production may thus be cancelled out by adverse environmental effects. Perennial crops, like cup plant ( Silphium perfoliatum L.), are said to benefit arthropods. Substituting silage maize could hence increase biodiversity and foster ecosystem services. This study aimed at comparing the attractiveness of both crops to arthropods, which are either flower-visiting or active in the crop canopy. Further, results were scaled to the landscape level to optimize crop partitioning concerning yields and species diversity. A field experiment with conventionally tilled annual and perennial no-tilled crops was established in 2015 near Munich (Germany). The crops chosen were insect-pollinated cup plant and wind-pollinated maize. Arthropods were sampled between June and September 2016. Four replicated UV-active pan traps, consisting of three bowls each, were used to catch arthropods at the actual crop height on five sampling dates. The collected arthropods were counted and taxonomically determined. In total 3810 individuals ( Arachnida : 52; Insecta : 3758) from 9 orders (115 taxonomic groups) were collected. Silage maize mostly showed lower diversity values, indicating higher biodiversity in cup plant. However, the differences were small. Nevertheless, cup plant harbored more pollinators and parasitoids. Finding an optimal combination of both crops based on diversity gains is thus not straightforward. However, integrating cup plant to silage maize production systems allows increasing arthropod diversity by means of moderate yield reduction. Graphical abstract: Image 1 Highlights: 3810 individuals from 115 taxonomic groups collected in silage maize and cup plant. Total species richness and abundance of arthropods are higher in cup plant. Cup plant fosters Hymenoptera and especially pollinators and parasitoids. Cup plant increases arthropod diversity by means of moderate silage maize yield reduction.